A NEW 800 mm AUTOMATIC TELESCOPE - Andrievsky, S. M.; Molotov, I. E.; Fashchevsky, N. N.; Podlesnyak, S. V.; Zhukov, V. V.; Kouprianov, V. V.; Kashuba, S. G.; Kashuba, V. I.; Mel’nichenko, V. F.; Gorbanev, Yu. M. (Одеські астрономічні публікації, 2013)
A new automatic telescope, a 800-millimeter main mirror catadioptric anastigmatic aplanat, was constructed by specialists of Odessa National University Astronomical observatory (Ukraine) in cooperation with their colleagues from the ISON project (Russia), and was recently put into operation. The telescope is mounted at Mayaki station in suburb ofOdessa. It is equipped with a focal corrector and a professional CCD camera. The telescope is used now for observations of geostationary objects, asteroids, and comets. In addition, this telescope can be used for the high precision photometric observations of faint objects up to 20m.